Ficcus palmata leaves as a low‐cost biosorbent for methylene blue: Thermodynamic and kinetic studies. (30th March 2019) - Fiaz, Rashida; Hafeez, Muhammad; Mahmood, Rashid
Abstract: In the present study, methylene blue (MB) removal has been studied from its aqueous solution, using Ficcus palmata leaves (FPL)‐based plant material. The effect of different parameters such as contact time (10–100) minutes, initial concentration (5–25) mg/L, pH (4–13), temperature (298–318 K), and adsorbent dosage (0.15–0.45 g/0.05 L) was investigated. The maximum removal efficiency was calculated to be 98% for sample having initial concentration 15 mg/L along with 0.45 g of adsorbent agitated for 80 min at 318 K and pH = 7. The data were fitted to adsorption isotherm models (Langmuir and Freundlich) and kinetic models (pseudo‐first order, pseudo‐second order, and intra‐particle diffusion). The data were found to be best fitted with Freundlich adsorption isotherm ( R 2 = 0.99) and pseudo‐second‐order ( R 2 = 0.991). Thermodynamic parameters (free energy change, enthalpy change, and entropy change) were also estimated. The Gibbs free energy values were found to be −1.808, −5.139, and −5.991 kJ/mol at 298, 308, and 318 K, respectively. The decrease in free energy with increasing temperature has indicated spontaneity of adsorption process, and positive enthalpy change (35.75 kJ/mol) showed that the adsorption process was endothermic. 0.1 M HCl was found to be most effective desorbing agent with percent desorption 53.51%. Practitioner points: FP leaves are low cost and easily available biomass for removal of MB from aqueous solution. The adsorption capacity was obtained to be 6.89 mg/g at (15 mg/g dye concentration, pH = 7, and contact time 80 min). The maximum removal efficiency for MB was 98%. The thermodynamic studies indicated the endothermic adsorption process. The 0.1 M HCl was found as best desorbing agent for MB loaded on FP leaves. Abstract : Ficcus Palmata leaves powder efficiently removed methylene blue (MB) from aqueous solution upto 98 %. Removal efficiencies depend on adsorbent dosage, pH, contact time, initial dye concentration and temperature. 0.1 M HCl was found to be the best desorbing agent for MB removal.